Protocolo empresarial en el proceso de venta en el Minimarket Anthony en la ciudad de Babahoyo - Montero Rodríguez, Víctor Hugo (2021)
The Anthony minimarket of the city of Babahoyo, aims to increase its general sales to position itself among the main stores in the local market. The sales protocol that the Minimarket has needs to be potentiated so that its workers, and on the part of the administration, provide better commercial marketing and thus see a continuous improvement for the Store and its customers. The improved attention oriented to an excellent customer service, under continuous supervision will gradually achieve that it is perfected by all and be carried as a form of attention as its daily mission, facilitating the training and integration of its new employees in the operation of as go within the minimarket, avoiding future financial losses. The protocol serves to achieve a good and harmonious coexistence in the workplace.